The Diagnostic Value of Procalcitonin in Patients with Severe Acute Pancreatitis: A Meta-Analysis - Lipeng Chen,; Jianbo Jiang, (Turkish Journal of Gastroenterology, 2022)
The role of procalcitonin in diagnosing severe acute pancreatitis has not been clearly assessed. This meta-analysis aims to evaluate the overall diagnostic accuracy of procalcitonin as a biomarker for severe acute pancreatitis. Medline (via PubMed), Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, and China WanFang Data were searched systematically for prospective studies reporting procalcitonin as a diagnostic marker of severe acute pancreatitis before August 31, 2021. Sensitivity, specificity, and other measures of the accuracy of procalcitonin in the diagnosis of severe acute pancreatitis were pooled by Stata 15.0 software. Heterogeneity was evaluated by I2 test, and the quality of included studies was evaluated by using the Quality Assessment of Diagnostic Accuracy Studies-2 system. Further, the sources of heterogeneity were verified using meta-regression and subgroup analysis, and the publication bias was evaluated by the Deeks’ funnel plot. A total of 18 studies meeting the inclusion criteria were included, containing 1764 patients. The pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio, and area under the receiver operating characteristic curve of procalcitonin for diagnosing severe acute pancreatitis were as follows: 0.80 (95% CI: 0.73-0.86), 0.84 (95% CI: 0.78-0.88), 4.95 (95% CI: 3.46-7.09), 0.23 (95% CI: 0.16-0.34), 21.26 (95% CI: 11.09-40.74), 0.89 (95% CI: 0.86-0.92). Also, P > .05 suggested no significant publication bias. Current evidence indicates that procalcitonin has good sensitivity and diagnostic accuracy for severe acute pancreatitis. However, the findings should be carefully used as routine evidence in diagnosing patients with severe acute pancreatitis alone because of the limited number of included studies and high heterogeneity.Cite this article as: Chen L, Jiang J. The diagnostic value of procalcitonin in patients with severe acute pancreatitis: A meta-analysis. Turk J Gastroenterol. 2022;33(9):722-730.